The Influence of Work Environment on Employee's Psychological Relationship: A Case Study of Japanese Literature. (24th May 2022) - Xin, Ziyu
Abstract : The new generation of employees grows up in the environment of rapid economic development, fierce competition, diversified values, and multiple channels of cultural communication, and their unique growth environment creates characteristics such as their unstable psychological state, poor adjustment ability, and significant self-awareness. The special psychological condition of the new generation employees will affect their own development and that of the organization. How to effectively manage the psychological capital of new generation employees has become an urgent problem for modern human resource management. Based on the social exchange theory and resource conservation theory, this study explores the relationship between the psychological capital of new generation employees and their job performance and propensity to leave and proposes research hypotheses and research models. Based on the survey data of 330 new generation employees, SPSS software was used to analyze the data and test the hypotheses. The psychological capital, job performance, and turnover tendency of new generation employees differed to different degrees in terms of age, education, years of work experience, and position level. The psychological capital of the new generation employees had a significant negative effect on the propensity to leave. Psychological capital had a significant positive effect on the relational performance dimension of job performance, and among the four dimensions of psychological capital, resilience and optimism had a significant positive effect on relational performance, while self-efficacy and hope had no significant effect on relational performance. The psychological capital of new generation employees mainly contributes to task performance through hope, resilience, and optimism and to relational performance through resilience and optimism.